IDENTIFIKASI DAMPAK INFRASTRUKTUR TERHADAP PERTUMBUHAN EKONOMI DI KABUPATEN SERUYAN - Eko Dedy Kurniawan; Tari Budayanti (Program Studi Manajemen Fakultas Ekonomi Universitas Balikpapan, 2024)
This research aims to identify the impact of road infrastructure development and its relationship to community economic growth in Seruyan Regency. Data analysis methods were used in this research. The results of the research are that road infrastructure in Seruyan Regency has not shown significant improvement. In fact, there are still roads in a seriously damaged condition. The condition of this road infrastructure is in line with the community's economic growth. Where the impact of road infrastructure is still not good, causing disruption to the community's economic transportation. So the rate of economic growth in society is also slow. This condition generally affects the poverty level of the community, where from year to year there is an increase in the poverty rate in Seruyan Regency.